(Re) Singularizações das práticas linguageiras de profissionais da educação mediadas por e-mail - Ramos, Aucélia Vieira (2019)
This research aims at investigating the work activity and the language practices of a llteam of educational professionals, describing the configuration of the writing of professional e-mails, based on the discursive relations present in the statements related to work activities. The hypothesis presented is that the e-mail is configured as a digital discursive genre that reveals the perspective of the professional activity to be performed, considering that the writing shows us the interactions that, although happening asynchronously, characterize the tensions and actions typical of the professional environment. Theoretically, the study is based on Ergology, current of studies that conceives human work as a situated activity, in which there are constant debates between the antecedent norms and the continuous choices made by the workers, and in the postulations of Bakhtin and the Circle on dialogism , constitutive of language activities. The research is a qualitative, and a field study was carried out, whose analysis unit was the 5ª Gerência Regional de Educação of the municipality of Campo Maior - Piauí, linked to the Secretaria Estadual de Educação do Piauí (SEDUC-PI). Observations were made at the institution which favored the selection of the documents, the e-mails produced and exchanged. Subsequently, interviews were conducted with two coordinators of the 5ª Gerência Regional de Educação, with a school director and a teacher from the state education network, in order to enable a better understanding of the context of the work activities studied and the concrete statements regarding language activities and their relationships with work activities. The analyzes show that the institutional enunciator present in the messages of the emails and in the speech of the interviewed professionals dialogues with the specific procedural knowledge of the work, anticipating an active response of adherence to the prescribed one necessary for the development of the tasks. The e-mail messages and the speech of the interviewed professionals also reveal the dialogical aspect between the prescribed one and the resubscriptions expressed as new modes of execution of the labor activities that situates the voices of the institution and the voices of the workers guaranteeing the legitimacy of the statements that effect work situations. The study allowed us to conclude that the work activity of the institutions and professionals researched is marked by several prescriptive aspects, but also by "dramatic" self-conflicts that guide workers in their arbitrations in order to keep their work activities stable through use of language.